Sustained Release Matrix Tablet: An Overview - Mehta, Mandev; S Keerthy, H.; Prasad Yadav, Rajkumar (Asian Journal of Pharmaceutical Research and Development, 2021)
Sustained Release is also a promising method for reducing medication side effects by preventing the therapeutic concentration of the drug from fluctuating in the body.The basic rationale of a sustained drug delivery system is to optimise a drug's biopharmaceutical, pharmacokinetic, and pharmacodynamic properties in order to maximise utility, minimise side effects, and cure the disease. The drug release rate is regulated by the matrix. HPMC and other release retardants can help with sustained release, so they are used as a key excipient in the formulation.The method entails compressing a mixture of medication, retardant material, and additives directly to shape a tablet with the drug embedded in a retardant matrix core; instead, granulation may be done prior to compression. Hydrophilic, hydrophobic, mineral, and biodegradable matrices may be used.To assess the drug release rate, in-vitro dissolution tests may be used. The primary goal of continuous release types is to improve drug therapy, which is determined by the relationship between the advantages and disadvantages of using one.